Law Enforcement of Spatial Planning Violations to Support Investment Balance and Environmental Sustainability in the Special Capital Region of Jakarta - Nugroho, Wahyu; Syahruddin, Erwin; Fahririn, Fahririn (Universitas Negeri Semarang, 2024)
This study addresses two primary research questions: first, what monitoring mechanisms has the government implemented for business actors regarding spatial use in Jakarta? Second, how is law enforcement concerning spatial planning violations in Jakarta oriented toward environmental sustainability? The objective of this research is to analyze both the supervisory mechanisms and the enforcement practices related to spatial planning violations, aiming to balance investment interests with environmental sustainability in Jakarta. The methodology employed includes normative and empirical juridical research, involving an inventory of relevant regulations and an examination of their enforcement in practice. Data collection is conducted through a sociolegal approach, involving interviews with local government officials and employing qualitative descriptive analysis. The findings reveal that the government’s monitoring mechanisms for business actors in Jakarta involve both active and passive supervision. Passive supervision includes responding to public complaints and reviewing issued permits, such as Environmental Impact Analyses (Analisis Mengenai Dampak Lingkungan, AMDAL). Additionally, preventive measures are implemented through AMDAL and other environmental permits, alongside ongoing environmental monitoring efforts. Active supervision involves field inspections based on a random sampling system of various business activities. Regarding law enforcement for spatial planning violations oriented towards environmental sustainability, the study finds that administrative sanctions are applied, including written warnings, building seizures, demolitions, and the closure of water channels. These sanctions are administered progressively, and law enforcement also integrates community participation.